Private secondary school students’ preference and perception on digital feedback mode for their English essay written work in online learning context - Loh, Koon Ying (2021)
If feedback delivered is ineffective, it would affect students’ willingness and interest to understand the feedback. 50 private secondary school students in Penang were invited to participate in this quantitative research. Based on the findings, students’ most preferred feedback mode is digital written feedback, followed by oral feedback, audio-visual recording feedback, and lastly, the least preferred feedback mode is voice recording feedback. Besides, most of them opted for understandable feature as the main factor that led them to prefer certain feedback modes. Thus, when providing feedback, simple yet powerful words should be utilised to ensure it would be more effective in improving their writing skill. Moreover, most of them perceive digital written feedback positively as they could review the permanent, understandable, detailed, clear or specific feedback whenever they want. Oral feedback is perceived as concise, detailed, understandable, less threatened and interactive, where they could seek instant clarification if they still have doubts. They agreed that voice recording feedback is personalised, understandable, less threatened, and useful for revision, where teacher’s tone would be revealed, and misinterpretation of the feedback message could be avoided. Lastly, for audio-visual recording feedback, they believed that it is understandable, detailed, and the quality feedback could engage them to revise through listening and watching. Apparently, this research has provided an insight for the teachers to understand the affordances of various digital feedback modes to cater to different learners especially when it comes to distance learning.